ANALISIS TINDAK PIDANA PERBANKAN YANG DILAKUKAN DALAM BENTUK PENYERTAAN (STUDI PUTUSAN NOMOR 664/PID.SUS/2021/PN PBR): Analysis of Banking Crimes Committed in the Form of Participation (Study of Decision Number 664/Pid.Sus/2021/PN Pbr) - Salsabilla Elfrida; Ermania Widjajanti (AMICUS CURIAE, 2025)
Banking Crimes encompass all actions that violate the provisions stipulated in the Banking Law. In the context of banking crimes, these offenses are characterized by their unique nature, particularly concerning the perpetrators who are employees within the banking sector. An example is the banking crime committed by Andri Syaryusman bin Syarmis, who served as the head teller at PT. Bank Pembangunan Daerah Riau. He was proven guilty of committing a banking crime under Article 49 paragraph (2) letter b of Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 on Banking, as examined based on the Pekanbaru District Court Decision Number 664/Pid.Sus/2021/PN Pbr. The data used in this analysis were secondary data, analyzed qualitatively, with conclusions drawn deductively. The research findings indicate that the judge did not rule in the form of participation in this banking crime because, in addition to the proven elements of the charged article in the fourth alternative indictment under Article 49 paragraph (1) letter b, the judge also considered the actions of the defendants, Andri Syaryusman and Nurhayati, separately. The form of participation identified in this banking crime is complicity, evidenced by the conscious collaboration and physical execution of the crime between Andri Syaryusman and Nurhayati.